INFLUENCE OF GIVING BREADFRUIT (Artocarpus altilis (Park) Fosberg.) LEAVES EXTRACT TO DECREASE URIC ACID LEVELS IN WISTARS RATS HYPERURICEMIC - Hagi Wibawa; Hikmah Fitriani; Rama Samara B; Irwan Meidi L (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Hyperuricemic is a condition where the uric acid levels in blood more than 7 mg/dl. In 2010, Hyperuricemic was included as one of non-communicable disease with incidence rate up to 30% and can cause the mortality. This study aims to examine the effective dose of breadfruit (Artocarpus altilis (Park) Fosberg.) leaves extract to decrease uric acid levels in Wistar rats Hyperuricemic.Methodology: This study was an experimental with pre-posttest with control group design. 30 Wistar rats aged three months was divided into 2 control groups (K1 and K2) and 3 treatment groups (K3, K4, and K5). Control groups were given purine (K1= standard, K2=high) and aquadest. Differently, treatment groups were given high purine and breadfruit leaf extract (K3=0.25g /KgBW, K4=0.5g /KgBW, K5=0.75g/KgBW). All the treatments were given one time daily in the morning for 7 days. Data were analyzed by the Shapiro-Wilk test followed by the One-Way ANOVA test and then Post-hoc Tamhane test.Result: The control groups revealed negative average reduction of uric acid in mg/dl (K1= -0.05, K2= -0.09) whereas the treatment groups revealed the positive average reduction of uric acid in mg/dl (K3=2.19, K4= 4.26, K5=5.87). The significant differences (p<0.05) of uric acid levels before and after treatment in each treatment groups had meaning that giving the Breadfruit leaf extract could reduce the uric acid level rats. Post-hoc Tamhane test result showed that the mean decrease of each group was significantly different. Particularly, K5 was the most effective treatment compared with others. Conclusion: Breadfruit leaves extract with dose of 0.75g/KgBW was the most effective treatment to reduce the uric acid level in blood. Stakeholders in health field should promote the Breadfruit as the traditional medicine method to reduce the uric acid in blood.